Margaret Thatcher et les marchés financiers : le paradoxe de la déréglementation - Marie-Claude Esposito (Revue Française de Civilisation Britannique)
Margaret Thatcher’s economic policy from 1979 to 1990 was meant to break away from the economic practices of successive post-war Keynesian governments. Fighting inflation was its first objective and reducing the government’s presence in the economy to improve its supply-side, and growth in particular, its second objective. As a result, markets were deregulated and state-owned industries were privatized. This article deals with the deregulation of financial markets whose contribution in terms of wealth, job creation and exports had been rising since the beginning of the 1970s. The strengths and weaknesses of the City of London are analysed in a first part and the deregulation of financial markets in a second part. The third section explains why the government introduced regulation into areas which had never been subject to statutory regulation, and why it broadened the scope of financial regulation and strengthened banking supervision.